Occupational Dualism and Intergenerational Educational Mobility in the Rural Economy: Evidence from China and India - M. Shahe Emran; Francisco H. G. Ferreira; Yajing Jiang; Yan Sun (Institute of Labor Economics (IZA), 2020)
This paper extends the Becker-Tomes model of intergenerational educational mobility to a rural economy characterized by farm-nonfarm occupational dualism and provides a comparative analysis of rural China and rural India. The model builds a micro-foundation for the widely used linear-in-levels estimating equation. Returns to education for parents and productivity of financial investment in children's education determine relative mobility, as measured by the slope, while the intercept depends, among other factors, on the degree of persistence in nonfarm occupations. Unlike many existing studies based on coresident samples, our estimates of intergenerational mobility do not suffer from truncation bias. The sons in rural India faced lower educational mobility compared with the sons in rural China in the 1970s to 1990s. To understand the role of genetic inheritance, Altonji et al. (2005) biprobit sensitivity analysis is combined with the evidence on intergenerational correlation in cognitive ability in economics and behavioral genetics literature. The observed persistence can be due solely to genetic correlations in China, but not in India. Father's nonfarm occupation was complementary to his education in determining a sons' schooling in India, but separable in China. There is evidence of emerging complementarity for the younger cohorts in rural China. Structural change in favor of the nonfarm sector contributed to educational inequality in rural India. Evidence from supplementary data on economic mechanisms suggests that the model provides plausible explanations for the contrasting roles of occupational dualism in intergenerational educational mobility in rural India and rural China.
Keywords: O12; J62; 330; educational mobility; rural economy; occupational dualism; farm-nonfarm; complementarity; coresidency bias; China; India